Awareness and sources of knowledge on men’s penile health in Lagos, Nigeria - Oscar Odiboh; Oladokun Omojola; Kehinde Oyesomi (Cogent Social Sciences, 2020)
Global attention to penile care is an aspect of men’s health within the Sustainable Development Goal 3 of the United Nations. Environmental and healthcare concerns about the connection between circumcision and penile care are real. According to the World Health Organisation, approximately 665 million males across the world are circumcised. However, social hush about penile problems as contributors to men’s life expectancy further incubates it for millions of men to suffer in silence. The purpose of this study is to open and direct healthcare attention to the dangers of penile disorder with an awareness check and knowledge sources. Designed questionnaire was operated on randomized 1,000 adults of equal gender distribution on mainland Lagos, Nigeria. Multi-stage cluster sampling technique was applied to carefully select a fair representation of study population. Newman’s health awareness theory and its applications by three other authors support this study. Results show that whilst men are more concerned about their penile performance, women showed extra interest in penile care and healthy usage. Open discussions and literatures on penile issues are rare in Nigeria. The study would spur public, academic and research interests in men’s penile health; by recommending the adoption of appropriate penile health policy within the SDG3 of the United Nations.